Digital STEM Learning to Enhance Critical Thinking in Elementary Science Education: Evidence from a Quasi-Experimental Study - Lalu Ibrohim Burhan (PT. LIB Research Cendekia, 2026)
Contemporary education increasingly emphasizes the development of higher-order thinking skills, particularly critical thinking, which plays a crucial role in enabling students to analyze information, evaluate evidence, and solve scientific problems. Although STEM-based learning has been widely recognized as an effective approach to promoting inquiry and problem-solving skills, its implementation at the elementary level often remains conventional and rarely integrates digital technologies systematically. This limitation creates a significant knowledge gap regarding how digitally integrated STEM learning environments can support students' critical thinking in science education. This study aimed to examine the effect of integrating a digital STEM approach on elementary students' critical thinking skills in science learning. A quasi-experimental design with a non-equivalent control group was employed involving 60 fifth-grade students from an elementary school in Indonesia. Data were collected through a rubric-based critical thinking test, classroom observation sheets, and a teacher perception questionnaire, and analyzed using descriptive statistics and t-tests. The results revealed that the experimental group demonstrated significantly greater improvements in critical thinking than the control group (t = 4.87, effect size = 0.82), with notable gains across the dimensions of analysis, evaluation, and problem-solving. These findings indicate that digital STEM integration fosters more interactive learning environments that enhance students' cognitive engagement in science learning. The study contributes theoretically by strengthening the linkage between STEM Education Theory and Critical Thinking Theory. It provides practical implications for the design of technology-supported science instruction in elementary education.